Exercise Behavior in the Context of Covid 19 Pandemic: An Abstract - Aydin, A.E. (Springer Nature, 2022)
The Covid-19 related restrictions have severe effects on individuals' ability to perform physical activities. As a result of the isolation measures, people stayed at home and could not sustain an active lifestyle. However, maintaining physical activity is even more critical during the pandemic considering its positive impact on mental well-being and its impact on general health (Dwyer et al. 2020; Matias et al. 2020; Teferi 2020). Given the importance of adherence to physical activity during the pandemic, understanding factors that influence exercise behavior is valuable. The objective of the study is to test a model of leisure-time exercise behavior that integrates participatory and regulatory motives in the context of Covid-19 pandemic conditions. It is suggested that physical participation motives, which relate to physical goals individuals try to achieve with exercise, influence regulatory motives, which relate to exercise behavior's underlying reasons (Ingledew and Markland 2008). The effects of isolation, positive and negative affect, amount of stress, and ability to handle stress on exercise participation motives and exercise behavior are also examined. An online survey is employed to gather data from 283 university students. The data is analyzed using structural equation modeling. The study results demonstrate that physical and psychological exercise participation motives are significantly associated with exercise behavior. Concerning the behavioral regulation constructs, it is revealed that intrinsic and introjected regulation predict exercise behavior. Additionally, while isolation and negative affect have a negative impact, coping with stress positively impacts exercise behavior. Moreover, it is shown that the indirect effects of participatory motives on exercise behavior are mediated by amotivation and intrinsic regulation. Finally, significant mediating effects of exercise participation motives are shown linking positive and negative affect, ability to cope with stress, and exercise behavior. The findings of the study provide practical implications for exercise promotion and intervention programs. For instance, since isolation and negative affect reduce exercise behavior, designing in-home physical activity routines, providing counseling for people, and teaching them stress reduction techniques such as meditation and breathing are recommended. Furthermore, it is suggested that emphasizing the fun aspect of exercise and avoidance of guilt may improve the persuasiveness of exercise promotion campaigns. © 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.
Keywords: Covid 19; Exercise Behavior; Isolation; Motives